DNase I and Sivelestat Ameliorate Experimental Hindlimb Ischemia-Reperfusion Injury by Eliminating Neutrophil Extracellular Traps - Wang CL; Wang Y; Jiang QL; Zeng Y; Yao QP; Liu X; Li T; Jiang J (Dove Medical Press, 2023)
Chun-Lian Wang,1 Yan Wang,2 Qi-Lan Jiang,3 Yang Zeng,4 Qing-Ping Yao,5 Xing Liu,6 Tao Li,7 Jun Jiang1 1Department of General Surgery (Thyroid Surgery), The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 2Department of Cardiology, The Fourth Hospital of Harbin Medical University, Harbin, People's Republic of China; 3Department of Clinical Nutrition, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 4Department of Orthodontics, The Affiliated Stomatological Hospital of Southwest Medical University, Luzhou, People's Republic of China; 5Institute of Mechanobiology & Medical Engineering, School of Life Science & Biotechnology, Shanghai Jiao Tong University, Shanghai, People's Republic of China; 6Department of Cardiology, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 7Key Laboratory of Medical Electrophysiology of Ministry of Education, Collaborative Innovation Center for Prevention and Treatment of Cardiovascular Disease, Institute of Cardiovascular Research, Southwest Medical University, Luzhou, People's Republic of ChinaCorrespondence: Jun Jiang; Tao Li, Email jiangjun@swmu.edu.cn; leta49@swmu.edu.cnPurpose: Neutrophil extracellular traps (NETs) play an important role in ischemia-reperfusion injury (IRI) of the hindlimb. The aim of this study was to investigate the effect of recombinant DNase I and sivelestat in eliminating NETs and their effects on IRI limbs.Patients and Methods: An air pump was used to apply a pressure of 300 mmHg to the root of the right hindlimb of the rat for 2 h and then deflated to replicate the IRI model. The formation of NETs was determined by the detection of myeloperoxidase (MPO), neutrophil elastase (NE), and histone H3 in the skeletal muscles of the hindlimbs. Animals were administered 2.5 mg/kg bw/d DNase I, 15 or 60 mg/kg bw/d sivelestat by injection into the tail vein or intramuscularly into the ischemic area for 7d. Elimination of NETs, hindlimb perfusion, muscle fibrosis, angiogenesis and motor function were assessed.Results: DNase I reduced NETs, attenuated muscle fibrosis, promoted angiogenesis in IRI area and improved limb motor function. Local administration of DNase I improved hindlimb perfusion more than intravenous administration. Sivelestat at a dose of 15 mg/kg bw/d increased perfusion, counteracted skeletal muscle fibrosis, promoted angiogenesis and enhanced motor function. However, sivelestat at a dosage of 60 mg/kg bw/d had an adverse effect on tissue repair, especially when injected locally.Conclusion: Both DNase I and moderate doses of sivelestat can eliminate IRI-derived NETs. They improve hindlimb function by improving perfusion and angiogenesis, preventing muscle fibrosis. Appropriate administration mode and dosage is the key to prevent IRI by elimination of NETs. DNase I is more valid when administered topically and sivelestat is more effective when administered intravenously. These results will provide a better strategy for the treatment of IRI in clinical.Keywords: ischemia-reperfusion injury, IRI, neutrophil extracellular traps, NETs, DNase I, sivelestat, hindlimb